Baby's First Picture: Ultrasound and the Politics of Fetal Subjects - Phillips, Catherine (Resources for feminist research, 2003)
It is difficult from her text to make any universal statements about a cultural role of ultrasound in women's lives, as the book follows the experience of heterosexual, male-partnered, able-bodied women, with income. There are of course women in Montreal who are single, disabled, and/or in common-law lesbian relationships who are having ultrasounds, and whose experiences differ on these bases (among others). Despite this sanitization, [Lisa M. Mitchell] rejects an identity-based race politic to define her research subjects, but notes the themes of race and culture in her analysis as contributing factors to women's experiences of fetal ultrasound. In this methodological regard, her recognition of the cultural complexity of technology and the analysis of normalcy (in contributing to an understanding of the fetal subject) are deficient due to the lack of representativeness of the interviewees. Though Mitchell does gesture to the profound desire to have a "normal" ultrasound (raised repeatedly by the sonographers and the women), this discussion would have benefitted from the inclusion of stories of, for example, a woman with a genetic disability and her contributions to a cultural theorizing of the desire for normalcy.